1998
DOI: 10.1111/j.1572-0241.1998.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Standard and High Dose Ranitidine on [13C]Urea Breath Test Results

Abstract: Ranitidine at standard or high doses did not generate a reproducible decline in breath test results. Histamine 2 blockers do not need to be discontinued before urea breath testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…7 According to Savarino et al, 6 the rate of a false-negative UBT after ranitidine administration is comparable to that after the administration of omeprazole. Although it has recently been reported that these drugs produce a false-negative test result, regardless of the dose, 12 there is no consensus of opinion regarding the effects of anti-ulcer drugs on the results of the UBT.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…7 According to Savarino et al, 6 the rate of a false-negative UBT after ranitidine administration is comparable to that after the administration of omeprazole. Although it has recently been reported that these drugs produce a false-negative test result, regardless of the dose, 12 there is no consensus of opinion regarding the effects of anti-ulcer drugs on the results of the UBT.…”
Section: Discussionmentioning
confidence: 91%
“…Much work has been done to document its high reproducibility, 8,9 but the accuracy of the test is significantly affected by the timing of the test and by the administration of anti-ulcer drugs. [3][4][5][6][7] One of the problems with the UBT is that a falsenegative result may be obtained if the test is performed soon after microbial eradication. Mucosal H. pylori levels and delayed recovery of the organism are considered to be some of the causes of a false-negative reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to avoid false-negative results, patients must not take proton pump inhibitors for at least two weeks before receiving the UBT (28,29). In contrast, histamine (H 2 ) blockers in standard dose do not seem to influence UBT results (29,30), whereas high-dose ranitidine requires a five days break (29,31). Decreasing the dead space contamination is important to reduce the measurement error in 13 C-UBT (32).…”
Section: Discussionmentioning
confidence: 90%